2017
DOI: 10.2147/mder.s132755
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter prospective study of patients undergoing open ventral hernia repair with intraperitoneal positioning using the<br />monofilament polyester composite ventral patch: interim results of the PANACEA study

Abstract: PurposeThis study assessed the recurrence rate and other safety and efficacy parameters following ventral hernia repair with a polyester composite prosthesis (Parietex™ Composite Ventral Patch [PCO-VP]).Patients and methodsA single-arm, multicenter prospective study of 126 patients undergoing open ventral hernia repair with the PCO-VP was performed. Patient outcomes were assessed at discharge and at 10 days, 1, 6, 12, and 24 months postoperative.ResultsAll patients had hernioplasty for umbilical (n = 110, 87.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 30 publications
0
22
1
1
Order By: Relevance
“…In a systematic literature review 77 including both open and laparoscopic primary ventral and incisional hernia repairs, it was concluded that there was no significant association between hernia recurrence and mesh overlap for open repairs. In a prospective case series 66 that used an intraperitoneal patch, there were no differences in mesh overlap between recurrent and non-recurrent hernias. In a recent retrospective study 78 of 1558 patients with a mean follow-up of 4 years, an overlap of less than 1 cm was associated with a higher recurrence rate in univariable analysis.…”
Section: Quality Of Evidence: Strength Of Recommendation: Weakmentioning
confidence: 92%
“…In a systematic literature review 77 including both open and laparoscopic primary ventral and incisional hernia repairs, it was concluded that there was no significant association between hernia recurrence and mesh overlap for open repairs. In a prospective case series 66 that used an intraperitoneal patch, there were no differences in mesh overlap between recurrent and non-recurrent hernias. In a recent retrospective study 78 of 1558 patients with a mean follow-up of 4 years, an overlap of less than 1 cm was associated with a higher recurrence rate in univariable analysis.…”
Section: Quality Of Evidence: Strength Of Recommendation: Weakmentioning
confidence: 92%
“…These complications are probably due to excessive traction on the straps in order to align the patch flatly against the parietal peritoneum [4, 7]. Although mesh misalignment may also have occurred in this series [8], as laparoscopic evaluation is the only way to verify this, the low recurrence (3%) and reoperation rate observed at the end of the 2 year follow up, show that at least the clinical impact of misalignment has been minimal. Nevertheless, accurate surgical technique with complete dissection of the falciform ligament cranially and the umbilical folds caudally is mandatory to obtain best patient outcomes, especially when using the largest 8.6 cm patch.…”
Section: Discussionmentioning
confidence: 95%
“…As reported in the early results of this prospective multicenter cohort study, patients underwent a small primary ventral hernia repair using the Parietex™ Composite Ventral Patch (PCO-VP) (Medtronic; Trevoux, France) with a diameter of 4.6, 6.6, or 8.6 cm, depending on the size of the defect [8]. The objectives were to assess hernia recurrence at 24 months follow-up and safety.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a multicenter prospective study, Berrevoet et al assessed surgeon satisfaction related to ease of mesh use in 95% of surgeries and reported an average surgical time of 36.2 minutes, favoring the open ventral patch technique. 14 Both surgical procedures represent minimally invasive techniques, therefore early mobilization of the patients is characteristic for these type of interventions. Vychnevskaia et al and Vorst et al highlighted the benefits of minimally invasive procedures.…”
Section: Primary Considerationsmentioning
confidence: 99%